Ostara: uma arquitetura de referência para coleta de dados em campo - SOUZA, Marcos Felipe Ferreira Amazonas de (Universidade Federal do Pará, 2020)
Data collection is an important and recurring process for decision making, which is present in different areas. In general, there are several solutions developed to aid field data collection activities. However, such solutions focus on solving specific problems, causing a lack of uniformity in relation to basic characteristics belonging to the domain of data collection. To supply the need for a domain knowledge repository this work proposed the development of a reference architecture (RA) that serves as a model for the construction of systems that bellong to the data collection domain model and the subdomain of mobile data collection.In order to elaborate the proposed reference architecture, the ProSA-RA process was used, this process helps the iterative and incremental development of reference architectures. This process is represented in four steps, which aim to structure the development of reference architectures. After the elaboration of RA using the ProSARA process, we tried to instantiate an architectural prototype to be able to evaluate execution-time qualities belonging to the proposed RA. The architectural prototype was modeled based on the business requirements of the "Banco de Germoplasma" project maintained by the Eletrobras Eletronorte Agency. This project seeks to maintain information regarding animal and botanic species of the Tucuruí - PA region. The instantiated and implemented architectural portion constitutes a tool for phenological monitoring of the botanical species of the project. The evaluation of the architectural prototype performed with the domain experts demonstrated runtime-related qualities such as performance, security, functionality and usability. However, the achievements of further evaluations to obtain quality metrics are necessary, such as the evaluation of development quality elements such as modifiability, portability, integrability and interoperability.